2010
DOI: 10.1080/13803391003662702
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive health benefits of strengthening exercise for community-dwelling older adults

Abstract: While aerobic exercise has been linked to improved performance on cognitive tasks of executive functioning among older adults, not all older adults can avail themselves of such exercise due to physical limitations. In this study, community-dwelling older adults were evaluated on tasks of executive functioning before and after a month-long strengthening, nonaerobic exercise program. A total of 16 participants who engaged in such exercise showed significantly improved scores on Digits Backward and Stroop C tasks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 30 publications
2
44
1
2
Order By: Relevance
“…While aerobic exercise is the most acknowledged form of exercise to reap cognitive benefits through cardiovascular and neurotrophic mechanisms inducing changes in brain health and activation, more recently, other types of exercise besides the cardiovascular one have attracted the attention of exercise and cognition researchers [10]. Muscular resistance training of yearly [45] or even monthly duration [50] seems to improve inhibition by enhancing functional plasticity of the cortex associated with inhibition processes [51]. This was observed, for example, with women aged 65 to 75 years by means of high intensity resistance training, even only once a week, of major muscle groups (arms flexions and extensions, seated row, upper limbs pull downs, leg press, legs flexions, and raises on ball of the foot), paralleled by specific strategies to promote participants' engagement [52].…”
Section: Discussionmentioning
confidence: 99%
“…While aerobic exercise is the most acknowledged form of exercise to reap cognitive benefits through cardiovascular and neurotrophic mechanisms inducing changes in brain health and activation, more recently, other types of exercise besides the cardiovascular one have attracted the attention of exercise and cognition researchers [10]. Muscular resistance training of yearly [45] or even monthly duration [50] seems to improve inhibition by enhancing functional plasticity of the cortex associated with inhibition processes [51]. This was observed, for example, with women aged 65 to 75 years by means of high intensity resistance training, even only once a week, of major muscle groups (arms flexions and extensions, seated row, upper limbs pull downs, leg press, legs flexions, and raises on ball of the foot), paralleled by specific strategies to promote participants' engagement [52].…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on the benefits of physical training have focused closely on aerobic exercise such as walking, and strength exercise, such as weight lifting 4,6,7,1012. These aerobic and strength exercises require the participants to be highly mobile.…”
Section: Introductionmentioning
confidence: 99%
“…The primary outcome measure is ST, which we selected because 1) previous studies using exercise training showed that exercise training can improve executive functions [45,46], 2) ST is a task that is often used to measure executive functions [47,48], and 3) ST has been standardized, with high reliability and validity in Japanese populations [39,49]. …”
Section: Methodsmentioning
confidence: 99%